LEGAL STANDING OF NOTARY COVERNOTE IN MAKING OF BANKING CREDIT DEEDS WHICH RESULT IN CRIMINAL ACTS OF CORRUPTION (CASE STUDY OF PANGKAL PINANG STATE COURT DECISION NO. 21/PID.SUS-TPK/2021/PN.PGP) - Munandar, Bima Yudhakusuma Putra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The role of a Notary in business activities is very important, especially in the banking sector because a banking activity requires legal certainty between debtors and creditors. The role of the Notary is very important in the legal certainty needed between the debtor and the debtor through an authentic deed made before a Notary. This study discusses the legal position of the Notary covernote in making bank credit deeds and the Notary's responsibility for making the covernote which resulted in the occurrence of corruption in the Pangkal Pinang District Court Decision No. 21/Pid.Sus-TPK/2021/PN.Pgp. The research method used is normative juridical research and explanatory research typology so that the results of this study are in the form of analytical explanatory. The results of the research in this thesis are that the covernote is not an authentic deed as stated in Article 1868 of the Civil Code and the covernote does not meet the requirements of an authentic deed as referred to in Article 38 of the UUJN. In addition, the results of this study also explain the responsibility of the Notary in the Pangkal Pinang District Court Decision No. 21/Pid.Sus-TPK/2021/PN.Pgp is a civil liability if there are parties who feel aggrieved or administratively liable to INI Association. Then, the Notary should explain the legal position of the covernote to the related parties that the covernote is only a certificate and the Bank should not use the covernote as the basis for credit disbursement, but still based on banking analysis and lending principles.Keywords: Covernote, Notary Responsibility, Corruption Crime